If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5x(5 + -7x) = 8 + -1(4x + 6) (5 * 0.5x + -7x * 0.5x) = 8 + -1(4x + 6) (2.5x + -3.5x2) = 8 + -1(4x + 6) Reorder the terms: 2.5x + -3.5x2 = 8 + -1(6 + 4x) 2.5x + -3.5x2 = 8 + (6 * -1 + 4x * -1) 2.5x + -3.5x2 = 8 + (-6 + -4x) Combine like terms: 8 + -6 = 2 2.5x + -3.5x2 = 2 + -4x Solving 2.5x + -3.5x2 = 2 + -4x Solving for variable 'x'. Reorder the terms: -2 + 2.5x + 4x + -3.5x2 = 2 + -4x + -2 + 4x Combine like terms: 2.5x + 4x = 6.5x -2 + 6.5x + -3.5x2 = 2 + -4x + -2 + 4x Reorder the terms: -2 + 6.5x + -3.5x2 = 2 + -2 + -4x + 4x Combine like terms: 2 + -2 = 0 -2 + 6.5x + -3.5x2 = 0 + -4x + 4x -2 + 6.5x + -3.5x2 = -4x + 4x Combine like terms: -4x + 4x = 0 -2 + 6.5x + -3.5x2 = 0 Begin completing the square. Divide all terms by -3.5 the coefficient of the squared term: Divide each side by '-3.5'. 0.5714285714 + -1.857142857x + x2 = 0 Move the constant term to the right: Add '-0.5714285714' to each side of the equation. 0.5714285714 + -1.857142857x + -0.5714285714 + x2 = 0 + -0.5714285714 Reorder the terms: 0.5714285714 + -0.5714285714 + -1.857142857x + x2 = 0 + -0.5714285714 Combine like terms: 0.5714285714 + -0.5714285714 = 0.0000000000 0.0000000000 + -1.857142857x + x2 = 0 + -0.5714285714 -1.857142857x + x2 = 0 + -0.5714285714 Combine like terms: 0 + -0.5714285714 = -0.5714285714 -1.857142857x + x2 = -0.5714285714 The x term is -1.857142857x. Take half its coefficient (-0.9285714285). Square it (0.8622448978) and add it to both sides. Add '0.8622448978' to each side of the equation. -1.857142857x + 0.8622448978 + x2 = -0.5714285714 + 0.8622448978 Reorder the terms: 0.8622448978 + -1.857142857x + x2 = -0.5714285714 + 0.8622448978 Combine like terms: -0.5714285714 + 0.8622448978 = 0.2908163264 0.8622448978 + -1.857142857x + x2 = 0.2908163264 Factor a perfect square on the left side: (x + -0.9285714285)(x + -0.9285714285) = 0.2908163264 Calculate the square root of the right side: 0.539273888 Break this problem into two subproblems by setting (x + -0.9285714285) equal to 0.539273888 and -0.539273888.Subproblem 1
x + -0.9285714285 = 0.539273888 Simplifying x + -0.9285714285 = 0.539273888 Reorder the terms: -0.9285714285 + x = 0.539273888 Solving -0.9285714285 + x = 0.539273888 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.9285714285' to each side of the equation. -0.9285714285 + 0.9285714285 + x = 0.539273888 + 0.9285714285 Combine like terms: -0.9285714285 + 0.9285714285 = 0.0000000000 0.0000000000 + x = 0.539273888 + 0.9285714285 x = 0.539273888 + 0.9285714285 Combine like terms: 0.539273888 + 0.9285714285 = 1.4678453165 x = 1.4678453165 Simplifying x = 1.4678453165Subproblem 2
x + -0.9285714285 = -0.539273888 Simplifying x + -0.9285714285 = -0.539273888 Reorder the terms: -0.9285714285 + x = -0.539273888 Solving -0.9285714285 + x = -0.539273888 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.9285714285' to each side of the equation. -0.9285714285 + 0.9285714285 + x = -0.539273888 + 0.9285714285 Combine like terms: -0.9285714285 + 0.9285714285 = 0.0000000000 0.0000000000 + x = -0.539273888 + 0.9285714285 x = -0.539273888 + 0.9285714285 Combine like terms: -0.539273888 + 0.9285714285 = 0.3892975405 x = 0.3892975405 Simplifying x = 0.3892975405Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.4678453165, 0.3892975405}
| 6p-5=7p+7-p | | h=-16t^2+100t+600 | | 15x^2-66x-45=0 | | 144+x^2=225 | | 84x^2-20xy+12x=0 | | 9/10y-3/5y | | 5x-20+11x-10+x+40=180 | | 12/(19x-4)=3/(5x) | | 81/y*3=27 | | a-15=22 | | 7(d-5)+9= | | 3a-12=36 | | -6x+4=-12 | | log(x)+log(x-1)=log(20) | | 15-8x=0 | | 26.8=4y | | 28+112-7+2= | | -17+8=m-5 | | 18a^3b^5+15b^2+5=0 | | 10/3 | | 8x^4-10x^3-4x=0 | | 14y*8=1034 | | 4c^2/1 | | 14y+35=9y+21 | | 3(k+12)=8-4k | | 14y*8=81 | | x-8=-6+9 | | 25x^2=-70x-49 | | 40-15=5(x-4) | | w+[-2.8]=4.3 | | 8w+w+8w= | | 7a+13+8=0 |